Raw Material Purchase Pattern in Seafood Plants in Kerala - A., Ramachandran; C.T., Samuel; N., Ranganathan (Fishery Technology, 2025)
Inadequate and irregular supply of raw materials arc the foremost problems faced by the processing plants in India. A study has been carried out on the purchase pattern of raw materials to aSSt.'SS the situation in the seafood plants of Kcrala, during 1983-84. 50% of the processing plants arc located within one krn from the main landing centre in a region. 82% of the plants have their own transportatlon facilities. 64% of the plants in Cochin region took 4 to 6 h for bringing the raw materials to the plants after purchase. This was between 6 and 8 h in Kollam region. In all the plants, the main item of purchase was confined to shrimps. The raw material purchases in all the plants were far below the installed capacity. In 39o/o of the working days, the plants selected for the study had no purchase or production during the study period.